The politics and practice of counting: Ethnicity in official statistics in Aotearoa/New Zealand - Cormack, Donna (Te Rōpū Rangahau Hauora a Eru Pōmare, 2010)
The politics and practice of counting: ethnicity in official statistics in Aotearoa/New Zealand was produced as part of a broader project funded by Te Kete Hauora, Ministry of Health to investigate issues with ethnicity data in New Zealand and the implications of these for the Māori health and disability sector. The paper is one in a series of topic-based discussion papers. It aims to summarise key literature on the measurement of the Māori population in official ethnic statistics over time as a background to the accompanying discussion papers.
Keywords: crown policy; ethnic identity; ethnicity; health; health outcomes; identity; policy; statistics

Oh, you don’t look Māori: Socially assigned ethnicity. - Cormack, Donna; Borell, Belinda; Gillon, Ashlea (MAI Journal: A New Zealand Journal of Indigenous Scholarship, 2019)
Keywords: blood quantum; ethnic identity; ethnicity; identity; kaupapa māori; racism; white privilege

The relationship between socially-assigned ethnicity, health and experience of racial discrimination for Māori: analysis of the 2006/07 New Zealand Health Survey - Harris, Ricci B.; Cormack, Donna M.; Stanley, James (BMC Public Health, 2013)
In New Zealand, there are significant and long-standing inequalities in a range of health outcomes, risk factors and healthcare measures between Māori (indigenous peoples) and Pākehā (European). This study expands our understanding of racism as a determinant of such inequalities to examine the concept of socially-assigned ethnicity (how an individual is classified by others ethnically/racially) and its relationship to health and racism for Māori. There is some evidence internationally that being socially-assigned as the dominant ethnic group (in this case European) offers health advantage.
Keywords: discrimination; ethnic identity; ethnicity; health; identity; inequity; racism; trauma